The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1108/sampj-04-2019-0150
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic capabilities and environmental accounting for the circular economy in businesses

Abstract: Purpose This paper aims to define and measure the environmental capabilities that are applied when the circular economy (CE) is introduced in businesses. Founded on the dynamic capabilities theoretical approach, the study analyzes different environmental competences that firms apply during this process. Environmental management systems, corporate social responsibility, reporting and accountability and other environmental accounting practices are studied in the same analytical framework used to study the enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(195 citation statements)
references
References 138 publications
3
124
0
6
Order By: Relevance
“…Some scholars argue that stakeholders' pressures positively affects the adoption of CE business models (Prieto-Sandoval et al, 2019). Scarpellini, Marín-Vinuesa, et al (2020) found that stakeholders' pressures directly affect the environmental capabilities for CE. Furthermore, such environmental capabilities mediate the relationship between stakeholders' pressures and the circular scope of a company.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars argue that stakeholders' pressures positively affects the adoption of CE business models (Prieto-Sandoval et al, 2019). Scarpellini, Marín-Vinuesa, et al (2020) found that stakeholders' pressures directly affect the environmental capabilities for CE. Furthermore, such environmental capabilities mediate the relationship between stakeholders' pressures and the circular scope of a company.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…There are plentiful empirical studies on the relation between DCs and performance. However, research on mediating mechanisms of DCs effects is very scarce (Zhou, Zhou, Feng, & Jiang, 2019 (Scarpellini, Marín-Vinuesa, et al, 2020). Notably, Zhu, Geng, and Lai (2010) contended that CE practices are positively related to the environmental and financial performance of a company.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…The studies aimed at understanding how the companies are integrating CE model in their activities is still limited and it is not clear how the CE activities must be reported within the company (Scarpellini et al, 2020).…”
Section: Circular Economy and Corporate Social Responsibility: Theorementioning
confidence: 99%
“…Some studied have indeed used CSR reports as a source to investigate the adherence of companies to this new model. The CE activities implemented by companies that is usually analysed in terms of "Triple Bottom line" of sustainability (Scarpellini et al, 2020), but the topic on how CSR and CE are related, is almost still unexplored.…”
Section: Circular Economy and Corporate Social Responsibility: Theorementioning
confidence: 99%
See 1 more Smart Citation